MODEL LOGISTIK ORDINAL UMUR KAWIN PERTAMA WANITA BALI - KENCANA, EKA N.; PRADNYASITA, IGA AYU RATIH; SUCIPTAWATI, NI LUH PUTU (E-Jurnal Matematika; Vol 13 No 3 (2024)DO - 10.24843/MTK.2024.v13.i03.p462, 2024)
Age at first marriage of woman is the difference between her birth date and date she began living with her spouse or partner, and is truncated to years. Age at first marriage of woman is well-known affects her healthiness and reproduction processes. Despite of Indonesian Law No. 16, 2019 regulated the marriage limit for woman and man is 19 years old, underage- or child-marriage are also happen in some parts of this country. This study models age at first marriage of Balinese women, by putting socio-demographics indicators as the predictor, i.e. woman’s educational level, parents’ educational level, family domicile area before marriage, family income, parents job, home ownership status, and number of family members. To study the causal relationship between age at first marriage of Balinese woman and its predictors, 270 women were proportionally selected from 9 regencies/city in Bali and asked to fill self administered questionaire. The data were analyzed by applying ordinal logistic regression. The result shows educational level of subjects as well their parents significantly affect age at first marriage of Balinese women while other factors do not demonstrate significant effect.